Non-antibiotic Isotretinoin Treatment Differentially Controls Propionibacterium acnes on Skin of Acne Patients - Ryan-Kewley, Angela E.; Williams, David R.; Hepburn, Neill; Dixon, Ronald A. (Frontiers in Microbiology, 2017)
Emergence and potential transfer of antibiotic resistance in skin microorganisms is of current concern in medicine especially in dermatology contexts where long term treatment with antibiotics is common. Remarkably, non-antibiotic therapy in the form of isotretinoin - a non-antimicrobial retinoid is effective at reducing or eradicating the anaerobe Propionibacterium acnes which is causally involved in the complex pathogenesis of Acne vulgaris. This study measured the extent of colonisation of P. acnes in patients with primary cystic or severe acne from three defined skin sites in ‘non-lesion’ areas before, during and after treatment with isotretinoin. Patients attending acne clinics were investigated using standardized skin sampling techniques and the recovery of anaerobic P. acnes from 56 patients comprising 24 females and 32 males (mean age 22y, age range 15-46y) who were given a standard course of isotretinoin (1mg/kg/day) are reported. P. acnes cultured from the external cheek surface of patients following treatment showed a significant reduction (1-2 orders of magnitude) compared with their pre-treatment status. Interestingly, other distinct sites (nares and toe web) failed to show this reduction. In addition, high levels of antibiotic-resistant P. acnes were recorded in each patients’ skin microbiota before, during and after treatment. In this study, microbial composition of the skin appears substantially altered by isotretinoin treatment, which clearly has differential antimicrobial effects on each anatomically distinct site. Our study confirmed that orally administered isotretinoin shows good efficacy in the resolution of moderate to severe acne that correlates with reductions in the number of P. acnes on the skin, including resistant isolates potentially acquired from previous treatments with antibiotics. Our study suggests that the role of tetracycline’s and macrolides, which are currently first line treatments in dermatology, might be reserved for severe or life-threatening infections since current antibiotic stewardship guidelines from medical departments no longer prescribe these antibiotics for routine use.